(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Four Cu-rich alloys from the ternary Cu-Al-Mn system were prepared in the electric-arc furnace and casted in cylindrical moulds with dimensions: f=8 mm and length 12 mm. Microstructural investigations of the prepared samples were performed by using optical microscopy (OM) and scanning electron microscopy, equipped by energy dispersive spectroscopy (SEM-EDS). Phase transition temperatures were determined using simultaneous thermal analyzer STA DSC/TG. Phase equilibria calculation of the ternary Cu-Al-Mn system was performed using optimized thermodynamic parameters from literature and Thermo-Calc software, TCW5. Microstructure and phase transitions of the prepared as-cast alloys were investigated and experimental results were compared with the results of thermodynamic calculations.